Evaluation of salivary cortisol and psychological factors in patients with oral lichen planus - Shah Bina; Ashok L; Sujatha G (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives: Lichen planus is a relatively common chronic inflammatory disease of oral mucosa and skin. Cortisol, also called as "stress hormone", has been used as an indicator in various stress evaluation studies. Salivary cortisol measurement is an indicator of free cortisol or biologically active cortisol in human serum and provides noninvasive and easy technique. Recent studies have been conflicting, and hence, in the present study, evaluation of salivary cortisol levels and psychosocial factors in oral lichen planus (OLP) patients was done. Materials and Methods: A total of 30 patients with clinically and histopathologically proven cases of OLP, along with the age and sex-matched healthy controls were included in the study. Samples of stimulated saliva were collected, centrifuged and analyzed for the level of cortisol with cortisol enzyme linked immunosorbent assay. Psychosocial factors of study and control groups were measured by depression anxiety and stress scale. Student′s t-test was used to compare the psychological factors and salivary cortisol levels between patients with the OLP and the control group. Results: Irrespective of sex, significantly higher depression (83.4 ± 15.4%), anxiety (80.5 ± 11.3%), and stress (94.2 ± 6.2%) scores were observed in OLP patients compared to controls. Increased cortisol levels were observed among 17 (56.6%) OLP patients in the study group. A positive correlation was found between psychological factors and salivary cortisol levels in the OLP patients. The values of Pearson′s correlation coefficient "r", between depression, anxiety, and stress with salivary cortisol was: +0.42,S; +0.27,NS; and +0.65,HS, respectively among the study group.